Penguatan Personil Branding Siswa melalui Pendidikan Kecakapan Hidup (Life Skills Education) di SD Islam Terpadu Logaritma Karanganyar Kebumen - Titi Maemunah (Jurnal Kridatama Sains dan Teknologi, 2021)
In order to empower the nation's young generation, education must be developed dynamically by following various progress that occurs in society. Thus, educational institutions must be functioned as the center for the development of intelligence and personality that are able to provide a strong generation and character. The development of a contextual and innovative education system becomes a positive effort for education institutions in preparing a truly qualified, independent and reliable generation of the nation. Therefore, SD IT Logaritma, apart from providing general knowledge and religion, also conducts personal branding through life skills education for students to survive the life. This research uses a qualitative approach with the type of case study research. Data collection techniques used are observation, interviews and documentation. While the data analysis technique used are inductive methods, deductive data interpretation and comparative methods. The result showed that the efforts to strengthen Student Personal Branding through Life Skills Education at SD IT Logaritma Karanganyar, Kebumen, were good enough. Life skills developed at SD IT Logaritma Karanganyar, Kebumen, included personal skills, thinking skills, social skills, academic skills and vocational skills. This condition was supported by the skills that students were interested to, it was shown from the activeness of students during the activity. The composition of the material was more practical than theoretical. The use of methods and approaches was appropriate according to the learning material and student conditions. In addition, the efforts to develop life skills were carried out in three stages, teaching; habituation and assignment stages; three processes of planning; implementation; and evaluation. Keywords: Personal Branding, Education, Life Skills, Life Skill Education